2014
DOI: 10.1016/j.cell.2014.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Autism-Associated Neuroligin-3 Mutations Commonly Impair Striatal Circuits to Boost Repetitive Behaviors

Abstract: Summary In humans, neuroligin-3 mutations are associated with autism, while in mice the corresponding mutations produce robust synaptic and behavioral changes. However, different neuroligin-3 mutations cause largely distinct phenotypes in mice, and no causal relationship links a specific synaptic dysfunction to a behavioral change. Using rotarod motor learning as a proxy for acquired repetitive behaviors in mice, we found that different neuroligin-3 mutations uniformly enhanced formation of repetitive motor ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
482
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(514 citation statements)
references
References 94 publications
28
482
2
2
Order By: Relevance
“…However, one previous investigation has indicated that female wild‐type mice show improved performance on the accelerating rotarod task across multiple strains (McFadyen, Kusek, Bolivar, & Flaherty, 2003). Phenotypic analyses of another monogenic model of ASD, the neuroligin‐3 ( NLGN‐3 ) knockout mouse, have noted enhanced motor learning in the rotarod task, similar to our Fmr1 KO females (Rothwell Patrick et al., 2014). The authors from Rothwell Patrick et al., 2014 suggested that several components of the motor routine become less variable with training such that latency to falling in this task could be considered an indicator of acquired repetitive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one previous investigation has indicated that female wild‐type mice show improved performance on the accelerating rotarod task across multiple strains (McFadyen, Kusek, Bolivar, & Flaherty, 2003). Phenotypic analyses of another monogenic model of ASD, the neuroligin‐3 ( NLGN‐3 ) knockout mouse, have noted enhanced motor learning in the rotarod task, similar to our Fmr1 KO females (Rothwell Patrick et al., 2014). The authors from Rothwell Patrick et al., 2014 suggested that several components of the motor routine become less variable with training such that latency to falling in this task could be considered an indicator of acquired repetitive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic analyses of another monogenic model of ASD, the neuroligin‐3 ( NLGN‐3 ) knockout mouse, have noted enhanced motor learning in the rotarod task, similar to our Fmr1 KO females (Rothwell Patrick et al., 2014). The authors from Rothwell Patrick et al., 2014 suggested that several components of the motor routine become less variable with training such that latency to falling in this task could be considered an indicator of acquired repetitive behavior. In accordance with these results, we suggest that perhaps female Fmr1 KOs display increases in acquired repetitive behavior in this task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4 D-G), all striatal-dependent symptoms observed in Fmr1 −/y mice (25)(26)(27)(28). Stereotypic behavior is indicated by an enhanced learning on the accelerating rotarod (24), mainly at late stages of learning (Fig. 4E).…”
Section: Fmrp Associates With One Main Mrna Species In Mouse Corticalmentioning
confidence: 99%
“…Remarkably, these alterations are similar to the one observed in FXS mouse model (6). Approximately 50% of patients with FXS also carry an autism diagnosis, and recent research on hallmark autistic symptoms point toward striatal dysfunction (23,24). To test whether Dgkκ loss of function could contribute to FXS phenotype, AAV9-delivered shRNA-Dgkκ was injected bilaterally into the striatum of wild-type mice.…”
Section: Fmrp Associates With One Main Mrna Species In Mouse Corticalmentioning
confidence: 99%